Dreaming the new woman: an oral history of missionary schoolgirls in republican China - Bond, Jennifer (Oxford oral history series, 2024)
"This book uncovers the voices of Chinese women who attended protestant missionary schools for girls in the early twentieth century. It is an oral history based on seventy-five interviews with alumnae from five girls' middle schools across East China including; McTyeire and St Mary's in Shanghai, Riverside Academy in Ningbo, Hangzhou Union Girls School in Hangzhou and the Laura Haygood School in Suzhou. In the past missionary schoolgirls have been labelled as 'foreign puppets' or seen as 'passive recipients' of a western-style education. This book puts at the centre of the analysis pupils own understanding of what it meant to be female, Chinese and possible Christian during the wars and revolutions of the first half of China's turbulent twentieth century. By focusing on the experience of women who attended these schools, this book provides fresh perspectives on the role of Christianity in the emergence of the Chinese New Woman. It explores how students experimented with new roles as they tried on overlapping school, Christian, patriotic, gendered and communist identities. In the process they envisioned a new form of gendered Christian modernity which became a part of an elite identity for Chinese women in the republican era"-- Provided by publisher